Perception Of Catch Marriage “Kawin Tangkap” Tradition - Renda, Trijuliani; Hendrik, Yandri Yusuf Cornelis; Tandjung, Ferofianes Linda; Koroh, Tince D.; Lepa, Ermanto Umbu (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Marriage in this century is arguably using the norm of romantic love. However, in the same century, a civilization performs a marriage with the term kawin tangkap which is quite viral on social media. This study aims to describe the perceptions of the people of Central Sumba who witnessed the reality of catch marriageusing three indicators of perception, namely knowledge, opinion and judgment as well as Talcott Parson's system theory. To dissect the factors behind this practice, Talcott Parson's theory of social action is used. The method used is qualitative method. The results of the study found that the community's perception is that the community knows exactly the process of the catch marriage tradition; the catch marriage tradition has shifted in meaning and practice, and considers that this catch marriage practice can be done if it is the path and in accordance with the actual tradition and should not be done if it is not in accordance with the tridasis. Meanwhile, the factors that cause this tradition to last are belis, debt and credit, the long customary marriage process and maintaining the line of descent.